Purchasing Decision Analysis in Modern Retail - Ridwan, Muhamad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
A consumer's decision to make a purchase is influenced by many factors, one of which is service. The better the company appreciates, serves, and facilitates customers, the consumers will always make the decision to make a purchase. This study aims to analyze the influence and contribution of service variables on purchasing decisions. The method used to study the phenomenon is quantitative. Data were collected through questionnaires, which were given to 97 respondents. The results of the study explain that service is one of the dominant factors that influence a consumer to make a purchase. The service indicator that is perceived to have the most influence is service friendliness. This implies the importance of having employees who have friendly and humanistic character or personality, so that they can maintain consumer relations with the company.